The Fundamentals of Advertising - Wilmshurst John (Butterworth Heinemann, 1993)
This book provides a comprehensive coverage of the whole business of advertising and its associated promotional areas (including PR, Sales promotion and sponsorship). Acknowledgements, Preface, What Advertising is About, What Advertising Does, How Advertising Does, How Advertising Happens, Picturing the Market, How the Advertising Business Functions, The Role of the Advertiser and the Importance of Briefing, How Advertising Works in Detail, The Printed Media, The Production of Advertising Material, Advertising Internationally, Index.